Financial and technical assessment of kenaf cultivation for producing fiber utilized in automotive components - Abdelrhman Mohammed, Hamdon Ali; Othman, Mohd. Shahwahid; Md. Tahir, Paridah; Abdul Samad, Abdul Rahim; Habib, M. A. A. E. I.; Ogeri, A. (Omics Publishing Group, 2016)
The kenaf plant is eco-friendly, renewable, low in cost and not meant to be a food source, owing to its potential commercial value in Malaysia, the government has allocated millions of ringgit for research to develop a viable kenafbased industry. This study is an attempt to assess the financial and technical performance of kenaf cultivation to produce fiber usage in automotive components. The financial data were collected through interviews with kenaf growers and from group discussions as well as production data collected from CMPC (Kenaf Processing and Marketing Centre) Bachok-Kelantan. The financial data were analyzed using Microsoft Excel software while Eview8 was used to analyze the production data. Three scenarios of kenaf production per hectare were assumed which were 15, 12 and 10 ton. According to the data analysis; the results revealed when kenaf production was 15 ton/ha, the farmer made a maximum profit of 37% from the subsidy provided by the Lembaga Kenaf Dan Tembakau Negara (LKTN) or National Kenaf and Tobacco Board, which was more than double the profit margin without subsidy. The financial analysis illustrated that all the three scenarios were viable when using the Benefit Cost Ratio (BCR) as an indicator. However, the production of 15 ton per hectare was the best of the three scenarios due to the five-year payback period, which was equal to half the period run on the model of the financial analysis. Additionally, the analysis of the production input (labor and chemicals) showed a significant effect on kenaf production as indicated in the analysis of Ordinary Least Square (OLS).